1985
DOI: 10.1002/cber.19851181205
|View full text |Cite
|
Sign up to set email alerts
|

Chemospezifität und Regioselektivität bei der Cycloaddition von Diazoalkanen an 1 H ‐1,2‐Diazepine

Abstract: 1H-I ,ZDiazepine 1 reagieren mit Diazoalkanen chemospezifisch, jedoch nur regioselektiv, an der 4-Doppelbildung zu ,,direkten" und ,,inversen" Pyrazolinodiazepinen (3,4,6 -21). Dabei nimmt die Reaktivitat von Diazomethan (DAM) uber Diazoethan (DAE) zu Diazoisopropan (DAP) deutlich zu, was mit MNDO-Rechnungen in guter Ubereinstimmung steht. Nach den AO-KOeffizienten der Grenzorbitale sollten diese konzertierten Cycloadditionen keine RegiospezifitBt, sondern nur eine gewisse Regioselektivitat aufweisen, was wied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…On evaluating a number of procedures, we found that adapting Streith46a,b and Kakehi’s36 protocols afforded a practically straightforward and expedient method. This could be generally applied for more elaborate substrates bearing different acyl functional groups from readily accessible electrophiles.…”
Section: Resultsmentioning
confidence: 99%
“…On evaluating a number of procedures, we found that adapting Streith46a,b and Kakehi’s36 protocols afforded a practically straightforward and expedient method. This could be generally applied for more elaborate substrates bearing different acyl functional groups from readily accessible electrophiles.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous experience, we selected a modification of pyrazolo [3,4-d] [1,2]diazepin-8-one. Of all the known publications [6][7][8][9][10][11][12][13] , the simplest and most convenient way to obtain it is the hydrazinolysis of 3,5-diphenylpyrano [3,4-c]pyrazole-8(1H)-one [11] . This approach is characterized by the simplicity of the reaction scheme, the use of inexpensive reagents, and allows a broad modification of the initial molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 1b: yield 58%; slightly yellow solid; mp 207À208 °C (lit. 18 mp 206 °C); 1 H NMR (400 MHz, CDCl 3 ) δ 8.60 (dd, J = 6.4, 1.0 Hz, 1 H), 7.83 (td, J = 7.8, 1.4 Hz, 1 H), 7.56 (apparent d, J = 8.2 Hz, 2 H), 7.48 (dd, J = 8.1, 1.5 Hz, 1 H), 7.43 (td, J = 7.7, 1.8 Hz, 1 H), 7.19À7.12 (m, 2 H), 2.43 (s, 3 H), 2.36 (s, 3 H); 13 C NMR (75 MHz, CDCl 3 ) δ 156. 3, 146.5, 141.3, 140.7, 138.0, 129.3, 128.0, 126.4, 123.9, 21.3, 19.9; LRMS (ESI) 285 (M + Na), 263 (M + H).…”
Section: ' Experimental Sectionmentioning
confidence: 99%